IMPLEMENTATION OF MULTIPLE INTELLIGENCE BASED LEARNING IN SD - Siska Mina Rita; Wilda Maulidiyah Saniyah; Nurul Imaniyah; Hofifah Rahmi Hayrani; Conny Dian Sumadi (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Intelligence is the ability to follow the knowledge, skills and expertise of a person to solve problems. In essence, every individual has several intelligences, including linguistic, mathematical, visual, spatial, kinesthetic, interpersonal, intrapersonal, musical and naturalist intelligences. However, the portion owned by each individual is not the same depending on how to develop all existing intelligence. With the birth of various types of intelligence that exist that each individual must understand, it is hoped that educators will not only assume that students who are smart and achievers are not academically intelligent. Because the potential of students in addition to the ability of the academic field only. All intelligences can be applied and can be companions independently of one another. In various theories of multiple intelligences, a teacher can indirectly master and learn with various learning methods. So that the function of the teacher here is as an educator, mentor, coach, advisor, reformer, creativity booster, generator, evaluator so that students succeed in optimizing.